Investigating Factors on Information Consumption by Software Developers on Software Ecosystem Portals - de Moura Parracho, Thiago; Oliveira Zacarias, Rodrigo; da Rocha Seruffo, Marcos César; Pereira dos Santos, Rodrigo (iSys - Journal of Information Systems, 2024)
Web portals play an important role within a Software Ecosystem (SECO), as they facilitate access to information and interaction among software developers over a common technological platform. However, developers' dissatisfaction with how information is presented on the SECO portal affects their engagement within the platform, causing a migration to consume information and interact in third-party channels, harming the SECO business model. In this context, this article aims to investigate the factors associated with the information consumption forms that influence software developers' decisions about where to seek knowledge about a SECO technological platform. To do so, we conducted a survey and a field study with developers to understand their information consumption in SECO portals. Results were analyzed from quantitative and qualitative approaches. Based on the results of the 50 responses from the survey, refined and complemented with the 14 interviews from the field study, we identified four sets of categories associated with factors that influence developers on where to seek knowledge about a SECO technological platform, from either SECO portals or third-party channels. As a contribution, we made four suggestions to favor developers' engagement and transparency in information consumption and interaction within SECO portals: 1) Creation or improvement of forums; 2) Improvement of official documentation; 3) Provision of content through videos; and 4) Provision of Artificial Intelligence (AI) to assist searches.